Cardiovascular Risk Factors in Women With Primary Sjögren's Syndrome: United Kingdom Primary Sjögren's Syndrome Registry Results1. Issue 5 (May 2014) - Juarez, M.; Toms, T. E.; de, P.; Mitchell, S.; Bowman, S.; Nightingale, P.; Price, E. J.; Griffiths, B.; Hunter, J.; Gupta, M.; Bombardieri, M.; Sutcliffe, N.; et al.
<x xml:space="preserve">Abstract</x> Objective To determine the prevalence of traditional cardiovascular risk factors using established definitions in a large cohort of clinically well‐characterized primary Sjögren's syndrome (SS) patients and to compare them to healthy controls. Methods Data on cardiovascular risk factors in primary SS patients and controls were collected prospectively using a standardized pro forma. Cardiovascular risk factors were defined according to established definitions. The prevalence of cardiovascular risk factors in the primary SS group was determined and compared to that in the control group. Results Primary SS patients had a higher prevalence of hypertension (28–50% versus 15.5–25.6%; P < 0.01) and hypertriglyceridemia (21% versus 9.5%; P = 0.002) than age‐ and sex‐matched healthy controls. Furthermore, a significant percentage (56%) of hypertensive patients expected to be on antihypertensive treatment according to best practice was not receiving it. Conclusion Primary SS patients are more than 2 times more likely to experience hypertension and hypertriglyceridemia than age‐ and sex‐matched healthy controls. Additionally, hypertension is underdiagnosed and suboptimally treated in primary SS.